Research on Naive Bayes Algorithm of Breast Cancer Diagnose Data by Machine Learning - Saket, Pushpraj; khurana, Anshul (International Journal of Computer Sciences and Engineering, 2025)
Breast cancer is one amongst the leading cancers for ladies in developed countries including Asian nation .It is the second most typical explanation for cancer death in women. The high incidence of breast cancer in women has redoubled considerably within the last years. Naïve Bayes algorithm is used for carcinoma identification Prognosis and diagnosis. Carcinoma Diagnosis is identifying of benign from malignant breast lumps and carcinoma Prognosis predicts once Breast Cancer is to recur in patients that have had their cancers excised. In this paper Naïve Bayes Algorithm is used to classify the Datasets of Breast Cancer (Diagnosis). The classification results show that when two features of maximum radius and maximum texture is selected, the classification improved accuracy is 98.6%, which is improved compared with previous method.